(3EOGQI GdYedjGJ GdfbOjI hGdeGdjI Hjf GdfXQjI hGdJWHjb (B/s - (3YGWa, RGgQ YHO GdQMjes ((3YeGf(B: s (3OGQ GdQGjI ddfTQ(B, s, 2008)
(3eGgjI GdfbhO,GdfXQjGJ GdfbOjI,GdfXGe GdfbOj,GdSjGSI GdfbOjI,ejRGf GdeOahYGJ hYedjGJgG GdfbOjI,GdJOabGJ GdfbOjI,GdSjGSI GdfbOjI,GdJTNjU GdeGdj hGdGSJQGJjLj ddeDSSI,GdSjGSI GdeGdjI,GdJMdjd GdeGdj,GdQbGHI GdeGdjI,GdShb GdfbOj hGdeGdj,eaGgje GdeUWdMGJ GdeGdjI hGdfbOjIs
(3HHdjhZQGajG(B:(3U U(B.301-302s
Keywords: (3GdEOGQI GdeGdjIs; (3GdfbhOs